A TRIZ-based Trimming method for Patent design around. (May 2015) - Li, Miao; Ming, Xinguo; He, Lina; Zheng, Maokuan; Xu, Zhitao
Abstract: Patent design around is an effective way to walk around competitive patents and avoid patent infringement. This paper proposes a TRIZ-based Trimming method for Patent design around. The 4 stages of Patent design around include design around target definition, design around problem identification, problem solving, and solution evaluation. In the 4 stages, Technical Features (TF) are identified to define design around target based on patent claim decomposition. In order to avoid literal infringement and doctrine of equivalents, the design around problem identification process of Trimming one or more patent Technical Features is developed. Then, the problem solving tools based on Modern TRIZ tools (such as Physical Contradiction resolution, and Function-Oriented Search) are introduced to solve the design around problem. Two Trimming scenarios of Core Ejector System is investigated to illustrate the method. The project successfully circumvents target patent and generates several new granted patents in China. Highlights: Establish an integrated TRIZ-based framework for Trimming strategy to design around competitive patent. Present a step by step Trimming Technical Features process to generate Trimming scenarios and Trimming problems for innovation inspiration. Generate two Trimming scenarios for Core Ejector System improvement.